Lysyl hydroxylase 3 modifies lysine residues to facilitate oligomerization of mannan-binding lectin. - Maija Risteli; Heli Ruotsalainen; Ulrich Bergmann; Umakhanth Venkatraman Girija; Russell Wallis; Raili Myllylä (PLoS ONE, 2014)
Lysyl hydroxylase 3 (LH3) is a multifunctional protein with lysyl hydroxylase, galactosyltransferase and glucosyltransferase activities. The LH3 has been shown to modify the lysine residues both in collagens and also in some collagenous proteins. In this study we show for the first time that LH3 is essential for catalyzing formation of the glucosylgalactosylhydroxylysines of mannan-binding lectin (MBL), the first component of the lectin pathway of complement activation. Furthermore, loss of the terminal glucose units on the derivatized lysine residues in mouse embryonic fibroblasts lacking the LH3 protein leads to defective disulphide bonding and oligomerization of rat MBL-A, with a decrease in the proportion of the larger functional MBL oligomers. The oligomerization could be completely restored with the full length LH3 or the amino-terminal fragment of LH3 that possesses the glycosyltransferase activities. Our results confirm that LH3 is the only enzyme capable of glucosylating the galactosylhydroxylysine residues in proteins with a collagenous domain. In mice lacking the lysyl hydroxylase activity of LH3, but with untouched galactosyltransferase and glucosyltransferase activities, reduced circulating MBL-A levels were observed. Oligomerization was normal, however and residual lysyl hydroxylation was compensated in part by other lysyl hydroxylase isoenzymes. Our data suggest that LH3 is commonly involved in biosynthesis of collagenous proteins and the glucosylation of galactosylhydroxylysines residues by LH3 is crucial for the formation of the functional high-molecular weight MBL oligomers.